Validity and Reliability of the Helkimo Clinical Dysfunction Index for the Diagnosis of Temporomandibular Disorders - Roger Alonso-Royo; Carmen María Sánchez-Torrelo; Alfonso Javier Ibáñez-Vera; Noelia Zagalaz-Anula; Yolanda Castellote-Caballero; Esteban Obrero-Gaitán; Daniel Rodríguez-Almagro; Rafael Lomas-Vega (Diagnostics, 2021)
The Helkimo Clinical Dysfunction Index (HCDI) is a simple and quick test used to evaluate subjects affected by temporomandibular disorders (TMDs), and its psychometric properties have not been tested. The test evaluates movement, joint function, pain and musculature, providing a quick general overview that could be very useful at different levels of care. For this reason, the aim of this study was to validate the use of the HCDI in a sample of patients with TMD. Methods: The sample consisted of 107 subjects, 60 TMD patients and 47 healthy controls. The study evaluated concurrent validity, inter-rater concordance and predictive values. Results: The HCDI showed moderate to substantial inter-rater concordance among the items and excellent concordance for the total scores. The correlation with other TMD assessment tests was high, the correlation with dizziness was moderate and the correlation with neck pain, headache and overall quality of life was poor. The prediction of TMD showed a sensitivity of 86.67%, a specificity of 68.09% and an area under the curve (AUC) of 0.841. Conclusions: The HCDI is a valid and reliable assessment instrument; its clinimetric properties are adequate, and it has a good ability to discriminate between TMD-affected and TMD-unaffected subjects.